Not all ultrasounds are created equal: general sonography versus musculoskeletal sonography in the detection of rotator cuff tears. Issue 4 (October 2016) - Cole, Brandi; Twibill, Kristen; Lam, Patrick; Hackett, Lisa; Murrell, George AC
Background: This cross-sectional analytic diagnostic accuracy study was designed to compare the accuracy of ultrasound performed by general sonographers in local radiology practices with ultrasound performed by an experienced musculoskeletal sonographer for the detection of rotator cuff tears. Methods: In total, 238 patients undergoing arthroscopy who had previously had an ultrasound performed by both a general sonographer and a specialist musculoskeletal sonographer made up the study cohort. Accuracy of diagnosis was compared with the findings at arthroscopy. Results: When analyzed as all tears versus no tears, musculoskeletal sonography had an accuracy of 97%, a sensitivity of 97% and a specificity of 95%, whereas general sonography had an accuracy of 91%, a sensitivity of 91% and a specificity of 86%. When the partial tears were split with those ≥ 50% thickness in the tear group and those < 50% thickness in the no-tear group, musculoskeletal sonography had an accuracy of 97%, a sensitivity of 97% and a specificity of 100% and general sonography had an accuracy of 85%, a sensitivity of 84% and a specificity of 87%. Conclusions: Ultrasound in the hands of an experienced musculoskeletal sonographer is highly accurate for the diagnosis of rotator cuff tears. General sonography has improved subsequent to earlier studies but remains inferior to an ultrasound performed by a musculoskeletal sonographer.